Rancang Bangun Absensi Mahasiswa Menggunakan RFID dan Sensor DS18B20 Berbasis NodeMCU Di Universitas Darul Ulum - Ferdiansyah, Prayogi; Sujatmika, Arif Rahman; Ummami, Izzatul (CV. Information Technology Training Center - Indonesia (ITTC), 2022)
Absence is something that must be done in the teaching and learning process, generally a university stipulates that attendance has a percentage of 10% on student assessments, besides that as a condition for taking semester exams students must have a total attendance of 50% of the number of meetings, it is not uncommon for students to cheat this by how to entrust absences to classmates. Based on these problems, an automatic attendance tool using NodeMCU-based RFID is made so that attendance is more efficient and there is no cheating. This tool reads the RFID serial number on the student's E-KTP. Absences can only be made according to the course schedule, so when there is no schedule, attendance cannot be made. Apart from that, as a prevention of the spread of the Covid-19 virus, the DS18B20 sensor was added to this tool to detect student temperatures. This sensor is programmed if the student's temperature exceeds 37°C, attendance will fail. To simplify the design of the tool, this study uses the prototype method. The case study was carried out at the engineering faculty of the informatics study program, Darul 'Ulum University, Jombang.